2015
DOI: 10.1038/ng.3415
|View full text |Cite
|
Sign up to set email alerts
|

Integrated molecular analysis of adult T cell leukemia/lymphoma

Abstract: Adult T cell leukemia/lymphoma (ATL) is a peripheral T cell neoplasm of largely unknown genetic basis, associated with human T cell leukemia virus type-1 (HTLV-1) infection. Here we describe an integrated molecular study in which we performed whole-genome, exome, transcriptome and targeted resequencing, as well as array-based copy number and methylation analyses, in a total of 426 ATL cases. The identified alterations overlap significantly with the HTLV-1 Tax interactome and are highly enriched for T cell rece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

58
1,036
6
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 696 publications
(1,119 citation statements)
references
References 60 publications
58
1,036
6
1
Order By: Relevance
“…We previously proposed that stimulation of the TCR/CD3 complex, represented by a low density of the CD3 antigen, is a unique feature of ATL/ATLL cells . A recent integrated molecular study of the ATL/ATLL genome also showed frequent alteration of TCR-nuclear factor κB signaling, which may suggest stimulation of ATL/ATLL cells through the TCR (Kataoka et al 2015). Gal-9 shows apoptotic activity toward tumor cells or T cells (Fujihara et al 2013), and it should be studied whether Gal-9 has an apoptotic effect on fresh ATL/ATLL cells.…”
Section: Discussionmentioning
confidence: 99%
“…We previously proposed that stimulation of the TCR/CD3 complex, represented by a low density of the CD3 antigen, is a unique feature of ATL/ATLL cells . A recent integrated molecular study of the ATL/ATLL genome also showed frequent alteration of TCR-nuclear factor κB signaling, which may suggest stimulation of ATL/ATLL cells through the TCR (Kataoka et al 2015). Gal-9 shows apoptotic activity toward tumor cells or T cells (Fujihara et al 2013), and it should be studied whether Gal-9 has an apoptotic effect on fresh ATL/ATLL cells.…”
Section: Discussionmentioning
confidence: 99%
“…-further develop whole-genome sequencing to identify hostassociated driver mutations in all conditions, as recently performed for ATL (Kataoka et al, 2015); -correlate the emergence of driver mutations with disease onset; -develop assays allowing early prediction of differential disease development and the identification of progression.…”
Section: Identify Biomarkers To Predict Disease Progressionmentioning
confidence: 99%
“…-genes promoting viral replication and persistence (Tax and HBZ) (Matsuoka and Jeang, 2007); -modes of viral entry and replication (infectious and mitotic cycles) (Ghez et al, 2010;Boxus et al, 2012;Gillet et al, 2011Gillet et al, , 2013Sibon et al, 2006); -genomic and epigenetic mechanisms leading to ATL (oncogenic stress, driver mutations) (Kataoka et al, 2015;Yamagishi et al, 2012); -the role of the immune response in the control of infection (Asquith and Bangham, 2008); -the pathogenic potential of HTLV-2, -3 and -4 (Calattini et al, 2006).…”
Section: Perform Basic Research To Unravel Mechanisms Of Viral Persismentioning
confidence: 99%
“…High-throughput methodologies were used to identify the cell of origin and to characterize commonly altered pathways in PTCL [51,5967]. These efforts were successful in defining characteristic gene expression profiles for AITL, ALK + ALCL, ATLL, and PTCL-NOS, identifying recurrent mutations and recognizing specific subtypes, which can now help to support correct diagnosis and classification of patients to distinct disease subgroups with different prognoses [46,59,60,62,63].…”
Section: Targets In Ptcl and Driver Mutationsmentioning
confidence: 99%